Development of an occupant model for far-side vehicle crashes. (9th November 2009) - Douglas, Clay; Fildes, Brian; Gibson, Tom
The biofidelity and performance requirements for a far-side occupant model are described. Previous work is analysed that highlights the potential use of a modified version of the TNO Human Facet Model for simulating far-side impacts. The model's biofidelity and performance are compared with PMHS results from pelvic offset sled tests, pendulum tests and a full-scale far-side crash test. Results indicate that the model exhibits good biofidelity compared with PMHS results, specifically its ability to simulate: belt interaction with the shoulder; loading to the pelvis, thorax and abdomen and whole body kinematics in a full-vehicle far-side crash. The model's main limitations are that its thorax is less capable of matching the magnitude of deflection observed in the PMHS pendulum tests.